Mesh‐Mould: Robotically Fabricated Spatial Meshes as Reinforced Concrete Formwork. (May 2014) - Hack, Norman; Lauer, Willi Viktor; Gramazio, Fabio; Kohler, Matthias
Abstract If robots are to be employed in the construction of high‐rise structures, logistics and material systems have to be entirely rethought to cater for both their abilities and limitations: robots have limited loading capacity, but greater dexterity than other on‐site, automated construction techniques. Here, Norman Hack of ETH Zurich and Willi Viktor Lauer of the Future Cities Laboratory (FCL) at the Singapore‐ETH Centre for Global Environmental Sustainability (SEC) describe the research they have undertaken to develop 'mesh‐mould' as an alternative to conventional formwork.